Faktor-faktor yang mempengaruhi kualitas audit - NOVIA WIJAYA (Jurnal Bisnis dan Akuntansi, 2016)
The purpose of this research is to obtain empirical evidence of the influence of independency, accountability, job experience, integrity, objectivity and professionalism on audit quality. The population in this research is all auditors who are working at public accountant office in Jakarta and has been registered on Indonesian Institute of Certified Public Accountants (IAPI). The sample of this research collected using purposive sampling. The resource data obtained from questionnaire. The number of questionnaire distributed was 150 copies, but only 134 questionnaire returned and 100 copies that can be used for this research. The statistical method used in this research is multiple regressions. The result of this research indicated that job experience and integrity have influence on audit quality. While independency, accountability, integrity, objectivity and professionalism have no influence on audit quality.